A városgazdálkodás modelljei. Nagykanizsa város gazdasági működése (1850-1914) - Kaposi, Zoltán (Közép-Európai Közlemények, 2014)
This study presents the practice of urban management in the ages of the dual monarchy through a domestic trading city. Nagykanizsa is a typical example of the quickly developing cities. In the second part of the 19th century more and more functions of the city came alive because of the increase in population and the development of the local economy. Incomes of the city were mainly coming from the management of the city’s own wealth and the surtaxes imposed on the citizenry. The improvement of the city’s infrastructure needed loans which resulted the serious indebtedness of the settlement. The most significant expenses of the city were the debt service, bureaucracy, social duties and the maintenance of public services. Two specific models evolved. At first, the city lent its own property and managed the rentals. The second model grew up around the turn of the century, when the city tried several times to run its own businesses in parallel with the rental model. This second model expanded between the two World Wars.